Nonlinear Maximum Power Point Tracking Control of Wind Turbine Based on Two-Mass Model Without Anemometer - Chen , Jian; Lu , Qun; Chen, Libing; Duan , Xiaohui; Yang, Boping; Duan , Wenyong; Zhang, Lanhong (Frontiers in Energy Research, 2021)
A nonlinear control without using anemometer is proposed to achieve the maximum power of the wind turbine (WT) based on two-mass model in this paper. To track the maximum power points, the optimal tip speed ratio control strategy requiring to know the optimal rotor speed of the WT (ORS) is employed. To achieve the ORS, a torque observer is designed to estimate the aerodynamic torque, then the ORS can be obtained by the corresponding calculations based on the estimated torque. Due to the high nonlinearities of the WT and time-varying wind speed, a nonlinear control based on feedback linearization control (FLC) is adopted to track the ORS. In the FLC, the WT is linearized firstly, then the rotor speed controller is designed via linear control technique. The effectiveness of the proposed control strategy is verified by simulation studies. The simulation results show that, compared with the traditional PI control based on torque estimation and FLC based on wind speed estimation, the proposed control strategy provide better dynamic performances and higher power conversion efficiency.